Metal‐Free Preparation of α‐H‐Chlorinated Alkylaromatic Hydrocarbons by Sunlight. Issue 27 (20th July 2018) - Gaspa, Silvia; Valentoni, Antonio; Mulas, Gabriele; Porcheddu, Andrea; De Luca, Lidia
Abstract: A metal and additive free process for the synthesis of benzyl chloride and α‐chloro alkyl arenes is reported. The proposed methodology can be carried out by the use of sunlight. The yield and conversion of the obtained benzyl chlorides are very high. Abstract : A new metal and additive free synthesis of benzyl chloride and α‐chloro alkyl arenes is reported. The proposed methodology is carried out by the use of sunlight or visible light. The yield and conversion of the obtained benzyl chlorides are very high. The product isolation procedure is very simple. The starting reagents as well as the visible light sources are inexpensive and readily available.